Assessing the economic and energy dimensions of circular economy investment and green taxation in the European Union - Ivanková, Viera; Taušová, Marcela; Cehlár, Michal; Khouri, Samer (Frontiers in Environmental Science, 2025)
IntroductionThe transition toward a greener and more circular economy has become a strategic priority within the European Union (EU), prompting a need to better understand the economic and energy implications of sustainable investment and fiscal instruments. The aim of this study was to examine the relationships between private investment to circular economy sectors, environmental and energy tax revenues, and selected economic and energy-related indicators in EU countries from 2014 to 2021.MethodsA variability analysis using the Kruskal-Wallis test was first applied to assess cross-country differences in indicator values. This was followed by pairwise correlation analysis to examine the strength and direction of associations among the indicators. Finally, a series of simple linear regression models was used to identify the extent to which green investment and fiscal variables were statistically associated with labor productivity, gross domestic product (GDP) per capita, energy intensity, and energy productivity.ResultsThe results showed that higher levels of green investment and fiscal revenues tented to co-occur with better economic performance, especially in terms of increased labor productivity and higher GDP per capita. However, the explanatory power of models concerning energy intensity and productivity remained limited, indicating the presence of other influencing factors. A variability analysis further revealed substantial disparities among EU countries, with Western and Northern European states consistently outperforming Eastern and Southern counterparts in terms of investment and tax levels.DiscussionThe findings indicated that both circular economy investment and environmental taxation were statistically related to economic and energy objectives, but their associations varied depending on broader institutional, policy, and structural conditions. These findings may provide useful insights for policymakers seeking to develop balanced strategies that align sustainability goals with economic performance.